2015
DOI: 10.5327/z1982-8470201500012309
|View full text |Cite
|
Sign up to set email alerts
|

Vibração de plantas de pimenta "malagueta" para produção de frutos e sementes em ambiente protegido

Abstract: Resumo: Objetivou-se verificar o efeito da vibração de plantas na produção de frutos e sementes e na qualidade fisiológica de sementes de pimenta "Malagueta", em cultivo protegido, com laterais abertas e fechadas. O experimento foi realizado na Fazenda Experimental da Faculdade de Ciências Agronômicas da Universidade Estadual Paulista (FCA/UNESP), município de São Manuel (SP). Foram dois tratamentos, que consistiram em plantas com e sem vibração. As plantas foram vibradas manualmente, balançando-se o arame ond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
1
Order By: Relevance
“…For fruit fresh weight, the irrigation levels with 75% WR led to higher means compared with the application of 100% WR (Table 1). Freitas et al (2015), applying the vibration treatment in the production of chili pepper, observed that the number of seeds per fruit (20 to 24) and fruit fresh weight (0.51 to 0.58 g) were inferior to those obtained in the treatments used in the present experiment. plants grown without bovine manure irrigated with 100% WR (L1) had a mean of 1.1 seeds fruit -1 ; plants irrigated with 75% WR (L2) had 2.48 seeds fruit -1 , and plants irrigated with 50% WR (L3) had 2.39 seeds fruit -1 .…”
Section: Resultscontrasting
confidence: 80%
“…For fruit fresh weight, the irrigation levels with 75% WR led to higher means compared with the application of 100% WR (Table 1). Freitas et al (2015), applying the vibration treatment in the production of chili pepper, observed that the number of seeds per fruit (20 to 24) and fruit fresh weight (0.51 to 0.58 g) were inferior to those obtained in the treatments used in the present experiment. plants grown without bovine manure irrigated with 100% WR (L1) had a mean of 1.1 seeds fruit -1 ; plants irrigated with 75% WR (L2) had 2.48 seeds fruit -1 , and plants irrigated with 50% WR (L3) had 2.39 seeds fruit -1 .…”
Section: Resultscontrasting
confidence: 80%